The Existence of Islamic Religious Education in the Era of Artificial Intelligence : An Analysis of Opportunities and Challenges in the 21st Century - Lorens, Xena; Haryati, Mita; Al Ghifari, Barkah; Rahmania, Elvina; Handayani, Tutut (Corolla International Conference, 2024)
In Islamic education in the digital era based on Artificial Intelligence, it is important to teach values such as integrity, responsibility, empathy, cooperation, and healthy time management in the careful use of digital technology. However, behind the many benefits that AI offers in the world of education, there are certainly challenges and risks, one of which is the decline in morals. Islamic education and artificial intelligence have significant consequences. One of them is the issue of ethics in the use of artificial intelligence in the field of education, which has become an absolute necessity for every academic and learner. This research uses a qualitative library research method with a descriptive-analytical approach, by collecting sources from various books and articles relevant to the existence of Islamic religious education in the era of artificial intelligence: an analysis of opportunities and challenges in the 21st century. The results of this research indicate that Islamic religious education in the era of artificial intelligence presents various opportunities and challenges that need to be addressed to ensure the continuity and relevance of this education in the 21st century. The opportunities that can be seized in Islamic religious education in the era of artificial intelligence include: Adaptive Learning, Chatbots and Virtual Assistants, Data Analysis, Simulations and Educational Games, Monitoring Student Development, Translation and Text Analysis. Meanwhile, the challenges faced in Islamic religious education in the era of artificial intelligence include: the displacement of scholars/teachers, dependence on technology, ethics and morality, potential influence of foreign cultures, and data security.